2019
DOI: 10.1080/09638237.2019.1581352
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic treatment – a systematic literature review and meta-analysis of qualitative studies

Abstract: Background: The literature on antipsychotic medication in psychosis lack systematization of the empirical knowledge base on patients' subjective experiences of using antipsychotic drugs. Such investigations are pivotal to inform large-scale trials with clinically relevant hypotheses and to illuminate clinical implications for different subgroups of individuals. Aims: To re-analyze and summarize existing qualitative research literature on patient perspectives of using antipsychotic medication. Method: A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 73 publications
4
37
0
1
Order By: Relevance
“…Mol (35) what can at times be uncomfortable and difficult discussions. This finding is consistent with a recent meta-analysis where patients preferred professionals who considered AP medication as one of many tools to achieve personal recovery (36), and a cornerstone of the recovery-oriented practice framework being to increase people's choice and self-determination in their health care (37,38).…”
Section: Optimal Care and Choices To Makesupporting
confidence: 89%
“…Mol (35) what can at times be uncomfortable and difficult discussions. This finding is consistent with a recent meta-analysis where patients preferred professionals who considered AP medication as one of many tools to achieve personal recovery (36), and a cornerstone of the recovery-oriented practice framework being to increase people's choice and self-determination in their health care (37,38).…”
Section: Optimal Care and Choices To Makesupporting
confidence: 89%
“…The passivity and occasional indifference described in several studies may also reflect the effects of neuroleptics on energy and motivation, or might alternatively be a manifestation of the negative symptoms of schizophrenia in some cases. A previous systematic review also highlighted loss of autonomy in neuroleptic users, identifying this as occurring in relation to early treatment of the acute stages of the condition, and suggesting that people regain a sense of agency as their condition stabilises [13]. In contrast, the current review found that across studies, there appeared to be a group of people who had fallen into a longterm state of passivity and hopelessness in relation to their neuroleptic medication.…”
Section: Discussionmentioning
confidence: 55%
“…Several qualitative studies have been conducted that describe the experiences of taking neuroleptics [13]. The rich nature of qualitative data means these studies can highlight the complex alterations to conscious experience, mental functions and behaviour that neuroleptics produce, arguably more successfully than quantitative approaches (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mange av deltakerne ga uttrykk for at de hadde behov for å snakke med noen som forstod hva de slet med, noe de mente at familie og venner ikke hadde forutsetning for. I en litteraturgjennomgang som så naermere på folks erfaringer med antipsykotisk medisinering, gjorde Bjornestad et al (2019) også funn som antydet at eksperthjelp ble sett som nyttig i en tidlig fase av behandlingen. I den medisinske modellen vil hovedansvaret for behandlingen nettopp ligge hos de profesjonelle.…”
Section: Hvordan Ivareta Mangfold Og Individuelle Behov?unclassified